The Effect of Fans’ Attitudes on Sponsorship Outcomes: Evidence from an Exploratory Study in Greece - Pantelis Nassis; Nicholas D. Theodorakis; Yannis Afthinos; Haralambos Kolybalis (Journal of Applied Sports Management, 2014)
This study examines the effect of sport involvement and fans’ beliefs about sponsorship on certain sponsorship outcomes in the context of professional basketball. Quantitative data were collected from a survey of 222 spectators attending a professional basketball game in Greece. A confirmatory factor analysis (CFA) was employed to examine the validity of the scale. Overall, the examination of the structural parameters indicated that attitude towards sponsors was significantly predicted by sport involvement and beliefs about sponsorship, while it significantly predicted purchase intentions, word of mouth, and fans’ satisfaction from the use of sponsor’s products.
Keywords: sport involvement; sponsorship; attitude toward sponsors; satisfaction; behavioral intentions